2021
DOI: 10.1088/1361-6404/ac2b04
|View full text |Cite
|
Sign up to set email alerts
|

Didactic laser speckle experiments with a lensless camera

Abstract: Laser speckles are granular patterns created through the interference of coherent light scattered by a rough surface. Besides comprising an appealing optical phenomenon, the speckle patterns enable applications in physical and biochemical measurements. This paper proposes didactic far-field (objective) speckle experiments using a visible laser source and a lensless webcam for implementation in optics labs or at home. Firstly, a ceramic mug works as the scattering surface to investigate the effect of the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Papers using laser speckle with didactic purposes have been published, e.g. [1][2][3][4][5]. However, the authors of the present work have not found educational papers reporting speckle techniques related to vibrations.…”
Section: Introductionmentioning
confidence: 86%
“…Papers using laser speckle with didactic purposes have been published, e.g. [1][2][3][4][5]. However, the authors of the present work have not found educational papers reporting speckle techniques related to vibrations.…”
Section: Introductionmentioning
confidence: 86%
“…The tests proceeded at room temperature, with environmental illumination absent and the setup mounted on a vibration‐free breadboard. The optical system and camera parameters are carefully adjusted to avoid saturation and improve the speckles contrast 19 . The algorithm evaluates both ZNCC and EZNCC (threshold empirically set as τ = 0.5) for the sake of comparison, yielding quantitative results regarding sensitivity, resolution, and dynamic range.…”
Section: Methodsmentioning
confidence: 99%
“…The size of this single speckle in the detector plane depends on the design of the experiment, particularly if we use or not a lens at the detector. For our measurements, we use a lens-less system, hence the size of a single speckle is equal to [146].…”
Section: Enhancement In Presence Of Variable Speckle Sizementioning
confidence: 99%